The Relationship Between Mindfulness, Depression, Anxiety, and Quality of Life in Individuals With Schizophrenia Spectrum Disorders - Bergmann, Niklas; Hahn, Eric; Hahne, Inge; Zierhut, Marco; Ta, Thi Minh Tam; Bajbouj, Malek; Pijnenborg, Geradina Henrika Maria; Böge, Kerem (Frontiers in Psychology, 2021)
Background: Schizophrenia spectrum disorders (SSD) are frequently accompanied by comorbid depressive and anxiety symptoms, as well as impaired quality of life (QoL). A growing body of evidence has demonstrated the relevance of mindfulness for SSD in recent years. The study examined the association between mindfulness, depression, anxiety, and QoL. Materials and Methods: A total of 83 participants with SSD were recruited at the in- and outpatient psychiatric hospital care. Participants completed the Southampton Mindfulness Questionnaire, Comprehensive Inventory for Mindful Experiences, and Freiburger Mindfulness Inventory, the Depression, Anxiety, Stress Scale to assess depression and anxiety, and the WHO-QoL Questionnaire. Multiple regression analyses examined the relationship between mindfulness and QoL and the mediating role of depression and anxiety. Results: Mindfulness had a significant statistical positive effect on QoL domains physical health, psychological, and environmental QoL in patients with SSD. Depression was identified as a significant mediator of this relationship. Conclusion: This study provides novel insight into mindfulness’ mechanisms and paves the way for a process-oriented approach to treat SSD. The results provide first evidence for the process-based value of mindfulness for SSD; future studies can focus on the role of mindfulness for central therapeutic processes of change by employing longitudinal designs.